1986
DOI: 10.1159/000132212
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic nucleolus organizer regions (NORs) in human testicular tumors

Abstract: Investigation of nucleolus organizer regions (NORs) in hematopoietic malignancies has indicated that the distribution and rearrangement of these regions may be more important in malignant tissues than is their number. In one of the few studies thus far reported on NORs in human solid tumors, we describe here Ag-NORs in a group of human testicular germ-cell tumors and the corresponding patients. Four of seven malignancies demonstrated consistent ectopic NORs; explanations could include chromosomal rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Our hypothesis that the distribution and rearrangement of NORs may be essential in tumor evolution is furthermore supported by the detection of ectopic NORs in human testicular tumors by DeLozier-Blanchet et al (1986. The results cited suggest that chromosome aberrations involving NORs could generally be important in tumor initiation and/or propagation.…”
Section: Discussionsupporting
confidence: 58%
“…Our hypothesis that the distribution and rearrangement of NORs may be essential in tumor evolution is furthermore supported by the detection of ectopic NORs in human testicular tumors by DeLozier-Blanchet et al (1986. The results cited suggest that chromosome aberrations involving NORs could generally be important in tumor initiation and/or propagation.…”
Section: Discussionsupporting
confidence: 58%
“…Nucleolar organizer regions are located on the five acrocentric chromosome pairs; 2 however, they have been reported in abnormal locations (ectopic NOR's) in human testicular tumors. 7 We also examined the expression of NOR's in the chromosomes of cultured cells from human brain tumors.…”
mentioning
confidence: 99%
“…In this context, it has been observed that TGCTs as well as GCNIS are characterized by enlarged hyperchromatic nuclei, clumped chromatin and, often, prominent nucleoli. Ectopic NORs have been described in primary germ cell tumors and in teratocarcinoma cell lines that could have been originated by chromosomal rearrangement or by derepression of preexisting inactive NORs [ 82 , 83 ]. All together these features indicate that rRNA synthesis is a potential target process for anti-cancer therapy and that inhibition of Pol I represents an attractive therapeutic approach to block ribosome biogenesis [ 84 ].…”
Section: Non-coding Rnamentioning
confidence: 99%